A computational fluid dynamics investigation of subsonic wing designs for unmanned aerial vehicle application. (December 2019) - Siddiqi, Z; Lee, JW
The wing of an unmanned aerial vehicle, RQ-7 Shadow, is modified to study the changes in the aerodynamics of the wing. The main focus is to investigate the effects of changing the components of wing design when the aircraft climbs and accelerates. These component modifications included changing the airfoil, planform, aspect ratio, and adding a winglet. Another objective is to study the efficacy of employing high-lift airfoils like the EPPLER 559 for subsonic unmanned aerial vehicle applications. For this, five wing designs are considered in this paper. Computational fluid dynamics simulations using ANSYS FLUENT® are conducted for each wing design. The C L /C D ratios for all the wings are calculated at increasing angles of attack (simulating Climbing) and increasing speed (simulating Acceleration). Compared to the NACA 4415 airfoil, which is utilized by the RQ-7 Shadow, the EPPLER 559 provides an increase in lift at the low angles of attack, but yields less of these benefits as the angle of attack increases. The tapered planform significantly reduces the high drag associated with the EPPLER 559 airfoil. The generation of higher lift forces with lower drag is further achieved by increasing the aspect ratio and through the addition of a winglet. When compared to the NACA 4415 airfoil, it is concluded that the EPPLER 559 airfoil is a viable candidate for subsonic unmanned aerial vehicle applications only when the components of wing design are altered. The performance of the wings that employ the EPPLER 559 airfoil improves when the planform is changed from rectangular to tapered, when the aspect ratio is increased and when a winglet is added.